The Role of the Work Environment on Career Development and Performance Motivation of Bank Jatim Bangkalan Employees - Alia, Maudina; Isa Anshori (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the most valuable assets owned by a company organization is human resources which are the main issue in the success of achieving a company's goals as employees as measured by career development and performance motivation. The aim of this research is to determine the importance of the work environment on career development and employee performance motivation. In this research, we observe the role of the work environment on career development and employee performance motivation at Bank Jatim Bangkalan. This research uses a qualitative approach where data sources are obtained from books, articles, journals, etc. as well as observing the internship process in progress so that research results are obtained which state that the role of the work environment plays a very important role in the career development and performance motivation of Bank Jatim employees Bangkalan